2005
DOI: 10.1097/01.ju.0000154618.40300.c8
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Function in Women With Pelvic Organ Prolapse Compared to Women Without Pelvic Organ Prolapse

Abstract: Pelvic organ prolapse appears to have a significant negative impact on sexual function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
52
5
4

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(65 citation statements)
references
References 11 publications
4
52
5
4
Order By: Relevance
“…As in our study, they did not find an association with orgasm incontinence and DOA. Their study was however much smaller (90 patients) and included patients with prolapse which may have influenced their results as prolapse can independently impact on sexual function [9,10]. Unlike our study, El Azab et al only asked about coital, penetration and orgasm incontinence rather than other parameters of sexual function.…”
Section: Discussionmentioning
confidence: 65%
“…As in our study, they did not find an association with orgasm incontinence and DOA. Their study was however much smaller (90 patients) and included patients with prolapse which may have influenced their results as prolapse can independently impact on sexual function [9,10]. Unlike our study, El Azab et al only asked about coital, penetration and orgasm incontinence rather than other parameters of sexual function.…”
Section: Discussionmentioning
confidence: 65%
“…A number of studies have demonstrated an association between pelvic floor disorders, including pelvic organ prolapse and urinary incontinence, and FSD [8][9][10][11]. A recent study of women over 40 seeking outpatient gynecology or urogynecology care found women with a higher burden of pelvic floor symptoms to be more likely to report infrequent orgasm, decreased arousal, and increased dyspareunia [11].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies suggest that pelvic organ prolapse may contribute to sexual dysfunction [2][3][4]. Relatively few studies have focused on sexual dysfunction after surgical repair of prolapse, particularly sexual function after the use of graft material.…”
Section: Introductionmentioning
confidence: 99%